The taxonomic, functional and phylogenetic diversity of birds in Xiaohongxiang Wetland, southwest China - Binqiang Li; Shaohui Zhang; Jie Guo; Shanjun Ma; Wenjie Zhang (Biodiversity Data Journal)
Small wetlands are essential for preserving global biodiversity, yet they are frequently neglected in conservation strategies due to vague definitions and a lack of research attention. In this study, we conducted thirty-six surveys via the point count method in the Xiaohongxiang Wetland, Anning City, Yunnan Province, China, from November 2023 to June 2024. We aimed to evaluate the impact of various habitats surrounding Xiaohongxiang Wetland (wetlands, villages, farmlands, cherry plantations and pine forests) on the taxonomic, functional and phylogenetic diversity of avian species and investigate the significance of these habitats for ecological conservation and restoration efforts. A total of 62 species were recorded. Small wetlands are vital for supporting common waterbirds, but may not safeguard rare species effectively. While cherry plantations and pine forests enhance avian diversity near wetlands, their low functional diversity could limit the ecological niches available to birds. This indicates that monoculture plantations might restrict the habitat variety needed for a diverse bird community. Our study found no clear phylogenetic clustering or overdispersion amongst bird species across habitats, suggesting that community assembly is shaped by competitive exclusion, habitat filtering and neutral processes. Despite a limited sample size, our results highlight a gap between taxonomic and functional diversity, indicating that multidimensional biodiversity metrics are essential for thoroughly evaluating wetland restoration and habitat impacts on bird diversity.